Preferencje ustrojowe jako czynnik dyskrepancyjny identyfikacji ideologicznych i partyjnych - Wojtasik, Waldemar (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
Apart from its institutional dimensions, the determining factors of the evolution of a political system are based on the social expectations concerning the possible shape of the preferred and implemented solutions. This paper presents the conclusions of nationwide research carried out on a representative sample (N=1086) to analyze the direction and scope of the expected change in the political system in relation to the political programs of the main political parties in Poland.